1998
DOI: 10.1007/bf02499150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated cold stress on intensity of lipid peroxidation and tissue antioxidant system

Abstract: Repeated cold stress performed in a cold-tempering mode reduces lipid peroxidation and activates tissue antioxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The most significant increase in SOD activity, induced by stress, was detected in the liver in our study. Increase in SOD activity suggests that cold stress may increase the rate of O -generation and subsequently H 2 O 2 formation (Emirbekov et al, 1998;Liu et al, 2000). All parts of the nervous system contain SODs: enzymes that remove superoxides by catalyzing their dismutations with one superoxide being reduced to H 2 O 2 and another oxidized to O 2 (Liochev and Fridovich, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant increase in SOD activity, induced by stress, was detected in the liver in our study. Increase in SOD activity suggests that cold stress may increase the rate of O -generation and subsequently H 2 O 2 formation (Emirbekov et al, 1998;Liu et al, 2000). All parts of the nervous system contain SODs: enzymes that remove superoxides by catalyzing their dismutations with one superoxide being reduced to H 2 O 2 and another oxidized to O 2 (Liochev and Fridovich, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Selman et al found that cold exposure (8 °C; 18 days) increased catalase activity in myocardial tissue of small mammals ( Microtus agrestis ) without altering superoxide dismutase activity [ 100 ] . Emirbekov et al observed that cold adaptation (-5 °C; 3 h; during 20–25 days) decreased the MDA level in the myocardium and increased total antioxidant activity in the myocardial tissue of rats[ 101 ]. We found that a free radical scavenger, N-2-mercaptopropionylglycine, abolished the infarct-reducing effect of cold adaptation [unpublished data].…”
Section: Introductionmentioning
confidence: 99%